2021
DOI: 10.1038/s41598-021-81953-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profiles in healthy nonhuman primates are blunted by sedation and demonstrate sexual dimorphism as detected by a validated multiplex immunoassay

Abstract: Cytokine profiling is a valuable tool for monitoring immune responses associated with disease and treatment. This study assessed the impact of sex and sedation on serum cytokines in healthy nonhuman primates (NHPs). Twenty-three cytokines were measured from serum using a bead-based multiplex assay. Assay validation for precision, sensitivity, recovery, linearity, and stability was performed. Samples from male and female cynomolgus and rhesus macaques either cooperating or sedated were compared. All cytokines e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Note that the normal ranges for cytokine levels in NHP are as follows: IL-6 0.3–1.2 pg ml −1 , TNF-α 1–10 pg ml −1 , IFN-γ 1.1–8.0 pg ml −1 (ref. 44 ). Data in d – f represent a single sample from each NHP receiving the test material within each single experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the normal ranges for cytokine levels in NHP are as follows: IL-6 0.3–1.2 pg ml −1 , TNF-α 1–10 pg ml −1 , IFN-γ 1.1–8.0 pg ml −1 (ref. 44 ). Data in d – f represent a single sample from each NHP receiving the test material within each single experiment.…”
Section: Resultsmentioning
confidence: 99%
“…f-h, Highest plasma levels of TNF-α (f), IL-6 (g) and IFN-γ (h) measured 0-24 h following drug administration (HER2-XPAT protein, n = 23 NHPs; HER2-uTCE, n = 8 NHPs). Note that the normal ranges for cytokine levels in NHP are as follows: IL-6 0.3-1.2 pg ml −1 , TNF-α 1-10 pg ml −1 , IFN-γ 1.1-8.0 pg ml −1 (ref 44)…”
mentioning
confidence: 99%
“…In this figure, reference cytokine levels for cynomolgus primates 40–47 are shown for each cytokine as a red dashed line. A tabular result for these studies is shown in Table_S3, where these baseline reference concentrations 46–54 are presented as highlighted values.…”
Section: Resultsmentioning
confidence: 99%
“…Six months after surgery, animals continued identical diets but with no restriction to quantity, after which sham animals continued to gain weight and demonstrate worsening metabolic control, to the extent that one animal became fully diabetic with subsequent weight loss. This model is uniquely well-suited for accurate assessment of metabolic parameters; the ability to perform clinically relevant oral and intravenous glucose tolerance testing with cooperative handling reduces the stress- and sedation-induced hyperglycemia ubiquitous in rodent studies ( Graham, 2017 ; Graham et al., 2012 ; Hocum Stone et al., 2021 ). We deeply characterized the metabolic profile of our cohort with HgbA1c, HOMA-IR, glucose disposal, and c-peptide levels, demonstrating that the sham group had increased peripheral and hepatic IR which is indicative of the metabolic syndrome which may lead to diabetes that is seen in the MUO clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized a highly translational animal, the macaque, with strong construct and face validity, while leveraging advantages of an animal model that cannot be performed in humans such as repeated sampling, dietary, and environmental control, and a sham surgical group. The translatability of this model is strengthened by the use of cooperative handling of the NHPs which results in less stress- and sedation-induced metabolic and immunologic perturbations often introduced by conventional handling techniques ( Graham et al., 2012 ; Graham and Schuurman, 2015 ; Hocum Stone et al., 2021 ). This model utilizes VSG, the most common treatment for obesity and the MetS ( Ikramuddin et al., 2013 ), to affect multiple interrelated biologic systems and address construct, face, and predictive model validity, thus bridging the gap between rodents and humans in anatomy, behavior, BA and microbiome diversity, and immunology.…”
Section: Introductionmentioning
confidence: 99%